The Student Movement at the University of Buenos Aires during the Last Military Dictatorship in Argentina (1976-1983) - Seia, Guadalupe Andrea (Anuario de Historia de América Latina, 2025)
In this article, I analyze the reorganization of the student movement during the last military dictatorship in Argentina (1976–1983). In the context of the Latin American Cold War, university youth engaged in political activism became a specific target of the systematic repressive plan perpetrated by the armed forces after the 1976 coup d’état. I describe how and why students managed to carry on with or began their educational and political activism despite universities being subject to state terrorism. Based on an empirical reconstruction from documentary sources and testimonies of former student activists at the University of Buenos Aires, I present a three-stage reorganization process with continuities and changes. I describe the kinds of actions (recreational, cultural, or political), revindications, and organizational methods based onthe heritage of the 1918 Reforma Universitaria (University Reform) that activists relied on to build an agenda of their own to contest higher education policies. I argue that the university student movement survived the dictatorship with notable changes but also continuities, becoming a respectable and notorious political actor during the transition to democracy in Argentina.